2003
DOI: 10.1128/aac.47.3.1137-1139.2003
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibilities of Shigella flexneri and Streptococcus pyogenes to Inner Gel of Aloe barbadensis Miller

Abstract: Aloe barbadensis Miller (or Aloe vera) has widespread use in health products, and despite numerous reports on the whole plant, little work has been performed on the inner gel, which has been used extensively in these products. This report describes the in vitro susceptibilities of two bacteria to this component

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 15 publications
1
71
0
4
Order By: Relevance
“…The MIC of Aloe vera gel for S. mutans was significantly less than that for periodontopathic bacteria, indicating that S. mutans was highly sensitive to Aloe vera gel, and higher antibacterial activity was observed against Gram-positive than against Gramnegative bacteria. The lower MIC of Aloe vera gel for Gram-positive bacteria, which has also been reported previously (20,26), might be related to the differences in cell wall structures of the two types of bacteria. Commercially available toothpaste containing Aloe vera extract has been investigated in a clinical trial and compared with fluoridated dentifrices.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The MIC of Aloe vera gel for S. mutans was significantly less than that for periodontopathic bacteria, indicating that S. mutans was highly sensitive to Aloe vera gel, and higher antibacterial activity was observed against Gram-positive than against Gramnegative bacteria. The lower MIC of Aloe vera gel for Gram-positive bacteria, which has also been reported previously (20,26), might be related to the differences in cell wall structures of the two types of bacteria. Commercially available toothpaste containing Aloe vera extract has been investigated in a clinical trial and compared with fluoridated dentifrices.…”
Section: Discussionmentioning
confidence: 77%
“…Saponins, which contain glycoside, are soapy substances that have both cleansing and antiseptic properties (30). It is noteworthy that some compounds like anthraquinones and saponin present in Aloe vera gel have direct antibacterial activities while some other components, such as acemannan, have been considered to exert indirect bactericidal activity through stimulation of phagocytosis (26,37). Therefore, based on the present data, we believe that the use of Aloe vera gel at optimum concentrations in toothpastes or mouthwashes could be useful for prevention of dental caries and periodontal disease.…”
Section: Discussionmentioning
confidence: 96%
“…Many reports are available on the antibacterial properties of these plants. The antibacterial activity of A. vera against Shigella flexneri and Streptococcus pyogenes has been documented (Ferro et al 2003). Extracts from A. vera also affect several Gram-positive and negative bacteria (Cock 2008).…”
Section: Discussionmentioning
confidence: 99%
“…[30,31] Another component acemannan has been considered to exert an indirect bactericidal effect through stimulation of phagocytosis. [32,33] The antimicrobial effect of ALV has been demonstrated in an in vitro study where it was reported to inhibit the growth of diverse oral microorganisms such as Streptococcus mutans, Streptococcus sanguis, Actinomyces viscosus, and Candida albicans [ . 34] ALV also has numerous anti-inflammatory agents like carboxypeptidase which inactivates bradykinin thereby reducing prostaglandin synthesis and inhibiting oxidation of arachidonic acid, which might decreases inflammation and relieves pain.…”
Section: Discussionmentioning
confidence: 99%